Spectrum of reproductive health problems for which adolescent girls seek consultation in hospital based adolescent clinic - Jain, Mudita; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescent girls in India are usually shy and hesitant in discussing reproductive health issues. Gradually this trend is changing with more adolescent girls seeking consultation in hospitals for these issues. The purpose of the present study was to analyze the reproductive health problems for which adolescent girls seek consultation in the adolescent clinic of Gynaecology department at a medical college hospital. Methods: A retrospective analysis of Adolescent clinic records was carried out at a medical college hospital in central India. The Gynaecology outpatient based Adolescent clinic records were analyzed for the presenting symptoms of girls attending this clinic over a period of two years (1st January 2013 to 31st December 2014). Results: A total of 1541 adolescent girls sought care in the Adolescent clinic of the Gynecology over the two year period. Of these, the majority consulted for menstrual irregularity (31%). The other reason for consultation was pain abdomen (18.8%), white discharge per vaginum (10.7%), dysmenorrhea (8.6%), urinary symptoms (5.6%), etc. Conclusions: The predominant health concern for which the adolescent girls seek consultation in hospital is menstrual irregularity besides dysmenorrhea and white discharge. Many of these issues can be addressed in adolescent school health education programs and may help alleviate the anxiety of young girls.